Molecular Interactions Between Polyurethane and UiO-66 in Polymer-MOF Nanocomposites: Microstructural and Mechanical Effects - S. Ahmad; M.F. Omar; E.M. Mahdi; K.A.A. Halim; S.Z. Abd Rahim; H. Md Akil; N. Nosbi; N. Yudasari; M.H. Hassan; S.S Md Saleh; M.B.H. Othman (Archives of Metallurgy and Materials)
The demand for polymer-based nanocomposite-reinforced nanoporous materials is becoming essential in sustainable development studies. Integrating nanoporous materials such as Metal-Organic Frameworks (MOFs) in polymer matrices is essential for developing sustainable advanced materials. Combining MOFs and polymer matrices can produce a hybrid material with improved mechanical strength and stability relative to its constituents. This study aims to elucidate the effect of synthesised UiO-66 nanoparticles in a polyurethane (PU) matrix on the subsequent hybrid materials’ microstructural and mechanical properties. UiO-66 nanoparticles were synthesised at 120°C, 130°C, and 140°C. The nanoparticles and subsequent nanocomposite were characterised using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Brunauer-Emmett-Teller (BET), and Field Emission-Secondary Electron Microscopy (FE-SEM). The experimental findings indicate that the UiO-66 nanoparticles synthesised at 130°C exhibited a highly desirable crystal structure and effective adsorption properties, and the nanoparticles synthesised at this temperature were then used to reinforce PU, forming a polymer-MOF nanocomposite. The mechanical properties of the resulting nanocomposite were determined using tensile and nanoindentation tests. The UiO-66 nanoparticles were incorporated into PU matrices at various weight percentages (10 wt.%, 20 wt.%, 30 wt.%, and 40 wt.%) via the solution casting technique. The results indicated that 30 wt.% UiO-66 in the polymer nanocomposite exhibits the best mechanical properties, and loading the polymer nanocomposite beyond 30 wt.% is more likely to result in nanoparticle agglomeration and brittle behaviours